Trend Analysis Techniques to Assist School Leaders in Making Critical Curriculum and Instruction Decisions - Gary D. Bigham; Mark R. Riney (Arizona State University, 2014)
As educational needs of students change in response to changing demographics, economic factors, workforce needs, and school accountability requirements, school leaders must continually monitor and adjust curricula and associated methods of instructional delivery to increase student learning. The analysis of student performance data is a critical component of curriculum decision-making processes, and the purpose of this study is to demonstrate an application of trend analysis techniques in making curriculum and instruction decisions using historical student performance data. The techniques are demonstrated in relation to a real school problem and are transferrable to similar problems facing other schools. This study underscores the importance school leaders should place on analyzing data when making decisions related to curriculum and instruction.